Evaluating the Implementation of Policy on Education Board - Herawati, Endang Sri Budi; Suryadi, Suryadi; Sujanto, Bejdo (International Journal for Educational and Vocational Studies, 2019)
This study was designed to discuss government policies on the Board Education, so conclusions can be obtained about these policies for the sake of improving the quality of education services. This study uses evaluation with a discrepancy evaluation model (DEM) consisting of four works: design, installation, process, and product. The data were collected through a combination of observation techniques, document studies, interviews, and questionnaires, with qualitative data analysis. The data sources in this study were the Education Board, the Education Office, DPRD, BAPPEDA, and several school principals who were deliberately chosen to collect research data. The results showed that unclear rules regarding funding sources for the Board Education was the main obstacle in the implementation of the work program. At the design and installation stage, there are no gaps, and policies have been applied by reference to existing rules. However, at the process and product stages, there are gaps where only a small number of programs have been prepared. This also results in a gap at the product stage, which results in the goal of forming an Education Board not being achieved. Work programs as operational roles and functions of the Board Education have been arranged according to the purpose of its formation. but limited budget and human resources were obstacles to optimizing the contribution of Board Education to improving the quality of education services. Full support from the government and regional government related to the allocation of funds for the operation of the Board Education, both through the allocation of APBD and through the Regulations of the Regent related to managing the allocation of Corporate Social Responsibility (CSR) activities from various companies in Cirebon District, so that improving the quality of education services can be more equitable, and the role of DUDI in developing education can be felt evenly throughout the Cirebon district. The Education Agency's readiness is needed to accept the presence of the Education Council as a strategic partner in the development of Education, and the need for delegation of authority related to the development and empowerment of the School Committee by the Education Board.